The Implementation of Deep Breathing Relaxation and Al-Quran Recitation in Reducing Acute Pain in Post-Op Sectio Caesarea Patients: A Study Case - Musviro Musviro; Ainun Syarifatul Fitriyah; Nurul Hayati; Laili Nur Azizah; Anggia Astuti (Health and Technology Journal (HTechJ), 2024)
Acute pain frequently affects post-cesarean section patients and, if left unmanaged, can slow recovery and potentially lead to chronic pain. Non-pharmacological methods like Deep Breathing Relaxation combined with Murottal Al-Quran therapy offer a promising solution to alleviate this pain. This case study examines the effectiveness of these techniques in reducing acute pain post-cesarean section in the Teratai Ward of Dr. Haryoto Regional General Hospital, Lumajang. Therapy involves daily 20-minute sessions of QS Ar-Rahman (78 verses) recited by Qori' Ahmad Saud via MP3. The participant was a patient meeting specific criterion: hospitalized for at least 3 days, with moderate pain levels (NRS score), exhibiting signs such as pain complaints, grimacing, protective behaviors, sleep difficulties, of Islamic faith, and with no hearing impairments. Pain levels were measured using the Numeric Rating Scale (NRS) before and after the intervention. Results showed a notable reduction in pain over the 3-day intervention, with the NRS score decreasing from 7 (moderate) to 4 (mild), accompanied by reduced grimacing, less protective behavior, and improved sleep quality. This study suggests that combining deep breathing relaxation and Murottal Al-Quran offers significant pain relief for post-cesarean patients. It is practical and cost-effective, allowing it to be easily implemented by nursing staff starting from the first-day post-surgery. These findings highlight a feasible approach for pain management in post-cesarean care, providing an effective and accessible option that aligns with the needs of Islamic patients, ultimately enhancing their comfort and recovery process.